The profile of young offenders in the City of Maputo, Mozambique - Niquice, Fernando Lives Andela (African journal of criminology and justice studies, 2018)
The present study describes the profile of 172 young people who were attending their prison sentences in three Maputo prisons. We examined their Certificates of Judgment and Execution of Sentence based on descriptive statistics and statistical tests. Most participants were male. Young people, especially men, committed a large number of crimes against property. There was higher prevalence of women committing crimes against people’s physical integrity and health. The number of young people charged increased as they progressed in age. The major part of the sample received correctional penalties, were convicted for the first time, had no occupation or worked in the informal sector, and came from the suburban neighborhoods of Maputo City. Our results show the need for focusing on the prevention of criminal acts in young people and in the monitoring of this population during and after incarceration.